PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI SMA - FARIDA NOVIYANTI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
This research is a Classroom Action Research which aims to improve students' activities and learning outcomes through the application of the Example non Example cooperative learning model in the Geography subject of Natural Disaster Mitigation material. The research subjects were students of SMA Negeri 5 Tebo class XI IPS 2 academic year 2021/2022 semester II totaling 29 people, consisting of 10 males and 19 females. The research was conducted in two cycles and was preceded by a pre-cycle. Each cycle is carried out with a time allocation of 2 meetings, each meeting consists of 2 hours of lessons (2 x 45 minutes). The instruments used are observation sheets and evaluation sheets. The data obtained are in the form of activity data and learning outcomes as well as supporting data for teacher activities and field notes. Indicators of research success are the activity data and student learning outcomes increase and the minimum percentage of activity is 75%, the value of learning outcomes is 75 and learning completeness is 75%. The results showed an increase in the percentage of students' learning activities in the Pre-Cycle 47.89%, increased to 66.67% in Cycle I and 78.93% in Cycle II. Learning outcomes also increased, namely the average value of 64.69 in the Pre-Cycle, then 73.83 in Cycle I and became 80.03 in Cycle II. Mastery learning also increased from initially 34.48% in the Pre-Cycle, in Cycle I to 72.41% and in Cycle II 86.21%. So that the purpose of this research is achieved that the application of the Example Non Example model can increase the activities and learning outcomes of students ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas yang bertujuan untuk meningkatkan aktivitas dan hasil belajar peserta didik melalui penerapan model pembelajaran kooperatif tipe Example non Example pada mata pelajaran Geografi materi Mitigasi Bencana Alam. Subjek penelitian adalah peserta didik SMA Negeri 5 Tebo kelas XI IPS 2 tahun ajaran 2021/2022 semester II yang berjumlah 29 orang, terdiri dari 10 laki-laki dan 19 perempuan. Penelitian dilakukan dalam dua siklus dan didahului pra siklus. Masing-masing siklus dilaksanakan dengan alokasi waktu 2 pertemuan, tiap pertemuan terdiri dari 2 jam pelajaran (2 x 45 menit). Instrumen yang digunakan berupa lembar pengamatan dan lembar evaluasi. Data yang diperoleh berupa data aktivitas dan hasil belajar serta data pendukung kegiatan guru dan catatan lapangan. Indikator keberhasilan penelitian adalah data aktivitas dan hasil belajar peserta didik meningkat dan minimal persentase aktivitas 75%, nilai hasil belajar 75 dan ketuntasan belajar 75%. Hasil penelitian menunjukkan peningkatan persentase aktivitas belajar peserta didik pada Pra Siklus 47,89%, meningkat menjadi 66,67% pada Siklus I dan pada Siklus II 78,93%. Hasil belajar juga meningkat, yaitu nilai rata-rata 64,69 pada Pra Siklus, kemudian 73,83 pada Siklus I dan menjadi 80,03 pada Siklus II. Ketuntasan belajar juga meningkat dari awalnya 34,48% pada Pra Siklus, pada Siklus I menjadi 72,41% dan pada Siklus II 86,21%. Sehingga tujuan penelitian ini tercapai bahwa penerapan model Example Non Example dapat meningkatkan aktivitas dan hasil belajar peserta didik